Mementoes and heritage objects related to Rev. Piotr Skarga - Jan Samek (Folia Historica Cracoviensia, 1996)
The article contains an overview of mementoes and heritage objects related to Rev. Piotr Skarga (deceased in 1612 in Krakow).